(untitled) (Web of Teachers: Inderscience Research, 2025)
This scientific article explores the psychological and neurophysiological aspects of the decision-making process of basketball players, focusing on the ability to make quick and accurate decisions. In high-level athletic performance, rapid decision-making is a key factor determining success. The article analyzes research and scientific theories that examine how basketball players apply their physical and cognitive abilities to make quick and accurate decisions. Neurophysiological processes and psychological factors, especially attention, memory, decision-making, stress management, and psychological preparation, are discussed in terms of how they influence game outcomes. Additionally, the article emphasizes the importance of considering neurophysiological and psychological aspects in the effective training of athletes.